Dying Swans and Madmen : Ballet, the Body, and Narrative Cinema - McLean, Adrienne L. (Book collections on Project MUSE., 2008)
The author explores the curious pairing of classical and contemporary, art and entertainment, high culture and popular culture to reveal the ambivalent place that this art form occupies in American life.